Defining Magic: A Reader (Critical Categories in the Study of Religion) - Otto, Bernd-Christian (Equinox Publishing Ltd., 2013)
Magic has been an important term in Western history and continues to be an essential topic in the modern academic study of religion, anthropology, sociology, and cultural history. 'Defining Magic' is the first volume to assemble key texts that aim at determining the nature of magic, establish its boundaries and key features, and explain its working. The reader brings together seminal writings from antiquity to today. The texts have been selected on the strength of their success in defining magic as a category, their impact on future scholarship, and their originality. The writings are divided into chronological sections and each essay is separately introduced for student readers. Together, these texts - from Philosophy, Theology, Religious Studies, and Anthropology - reveal the breadth of critical approaches and responses to defining what is magic